2021
DOI: 10.3892/or.2021.8022
|View full text |Cite
|
Sign up to set email alerts
|

Hypochlorous acid selectively promotes toxicity and the expression of danger signals in human abdominal cancer cells

Abstract: Tumors of the abdominal cavity, such as colorectal, pancreatic and ovarian cancer, frequently metastasize into the peritoneum. Large numbers of metastatic nodules hinder curative surgical resection, necessitating lavage with hyperthermic intraperitoneal chemotherapy (HIPEC). However, HIPEC not only causes severe side effects but also has limited therapeutic efficacy in various instances. At the same time, the age of immunotherapies such as biological agents, checkpoint-inhibitors or immune-cell therapies, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…HOCl adduction of relevant molecular targets remains poorly understood, and apart from modulation of inflammatory pathways HOCl has also been shown to display cancer cell-directed activities including GRP78-mediated modulation of ER stress, autophagy, and proteotoxicity. Specifically, GRP78-directed Lys353 oxidation and other molecular pathways have been involved in HOCl-associated antitumorigenic activity, a topic to be explored by future experiments in the context of HOCl-suppression of photocarcinogenesis [ 9 , 66 , 67 ]. Additionally, upregulation of the tumor suppressor gene Txnip observed by us in response to HOCl-exposure in the context of our UV-induced SKH-1 high risk mouse model might also be involved in the anti-tumorigenic activity of topical HOCl ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HOCl adduction of relevant molecular targets remains poorly understood, and apart from modulation of inflammatory pathways HOCl has also been shown to display cancer cell-directed activities including GRP78-mediated modulation of ER stress, autophagy, and proteotoxicity. Specifically, GRP78-directed Lys353 oxidation and other molecular pathways have been involved in HOCl-associated antitumorigenic activity, a topic to be explored by future experiments in the context of HOCl-suppression of photocarcinogenesis [ 9 , 66 , 67 ]. Additionally, upregulation of the tumor suppressor gene Txnip observed by us in response to HOCl-exposure in the context of our UV-induced SKH-1 high risk mouse model might also be involved in the anti-tumorigenic activity of topical HOCl ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HOCl-hydrogel formulations have shown immunotherapeutic efficacy against experimental murine melanoma (176). Consistent with these observations, a suppressive role of HOCl in the control of cancer cell viability and tumor progression has been envisioned and further substantiated (71,177,178).…”
Section: Potential Therapeutic and Chemopreventive Opportunities Of T...mentioning
confidence: 66%
“…[ 30 ] In addition, it was also reported that DAMP emission could be different for the same cancer cell lines depending on in vitro or in vivo treatment. [ 31 ] To evaluate the ICD induction and anti‐tumor immune response of our BSA/TPA‐Erdn nanoparticles in vivo, an NSG mice model without the immune system (T\B\NK cells) was built. Such an NSG mice model provides the opportunity to evaluate MM patients’ immune responses induced by our BSA/TPA‐Erdn, and its antitumor performance on human MM cell lines.…”
Section: Resultsmentioning
confidence: 99%